Trend of influenza before and during the COVID-19 pandemic in Nepal-A study from 2018 to 2022. - Smriti Shrestha; Priya Jha; Lilee Shrestha; Lok Bandhu Chaudhary; Rashmi Mulmi; Arunkumar Govindakarnavar; Runa Jha (PLoS ONE)
A significant reduction in influenza incidence during the early days of COVID-19 pandemic was reported worldwide. This study aims to understand the impact of public health and social measures implemented during the COVID- 19 pandemic on influenza circulation in Nepal. We utilized influenza sentinel and non-sentinel surveillance data from Nepal between 2018 and 2022, obtained from the National Influenza Centre (NIC) at National Public Health Laboratory (NPHL), Nepal. Additionally, we used publicly available national COVID-19 case data released by the Ministry of Health and Population of Nepal. The data were analyzed for the trends in influenza cases, positivity rate and the distribution of subtypes/lineages. Furthermore, we compared the trend of influenza with that of COVID-19 and the social and public health measures implemented in the country as part of the COVID-19 response. The average influenza positivity rate dropped significantly from 39% to 14% during the COVID-19 period compared to the pre- COVID-19. Additionally, during the time of COVID 19 there has been a shift in the influenza bimodal seasonal pattern, with only one peak observed. Influenza type A consistently dominated, with variations in its subtype observed from year to year. Notably, one case of Influenza A/H5N1 was reported in 2019. This study shows that the influenza positivity rate decreased substantially after the COVID-19 pandemic began, possibly due to the stringent public health and social measures implemented during the pandemic. Adaptation of the influenza surveillance system during pandemics and integration of other respiratory pathogens into it not only allows continuity of surveillance but also helps to evaluate the public health and social measures implemented to manage future respiratory virus pandemics.